Spatio-temporal propagation dynamics of Airy plasmon pulses - Singh, Amit; Pertsch, Thomas (Optics Express, 2022)
We investigate numerically the evolution of a particular type of non-diffracting pulsed plasmonic beam called Airy plasmon pulses. A suitable diffraction grating is obtained by optimizing a grating (e.g., [Phys. Rev. Lett. 107, 116802 (2011)]) for maximum generation bandwidth and efficiency to excite ultrashort Airy plasmon pulses. The optimization process is based on Airy and non-Airy plasmons contributions from the diffraction grating. The time-averaged Airy plasmon pulse generated from the grating shows a bent trajectory and quasi non-diffracting properties similar to CW excited Airy plasmons. A design-parameter-dependent geometrical model is developed to explain the spatio-temporal dynamics of the Airy plasmon pulses, which predicts the pulse broadening in Airy plasmon pulses due to non-Airy plasmons emerging from the grating. This model provides a parametric design control for the potential engineering of temporally focused 2D non-diffracting pulsed plasmonic beams.
CRIS-Team Scopus Importer:2023-04-20